The Effect of Leverage, Company Size, and Executive Characteristics on Tax Planning - Ratna Zebua; Lusiana Lusiana; Ronni Andri Wijaya (Lembaga Penelitian dan Pengabdian Kepada Masyarakat Universitas Putra Indonesia YPTK, 2020)
This study aims to determine the effect of Leverage, Company Size, and Executive Characteristics on Tax Planning with Profitability as a Control Variable in Manufacturing companies listed on the Indonesia Stock Exchange 2014-2018. The sample in this study amounted to 65 manufacturing companies taken through purposive sampling. The data used is secondary data, and the analytical method used is multiple linear regression analysis. The results of this study indicate that 1) Leverage has a significant effect on tax planning. 2) Company size has no significant effect on tax planning. 3) Executive characteristics have no significant effect on tax planning. 4) Leverage, company size, and Executive Characteristics have a significant effect on tax planning together. 5) Leverage has no significant effect on tax planning with profitability as a control variable. 6) Firm size has a significant effect on tax planning with profitability as a control variable. 7) Executive characteristics have no significant effect on tax planning, with profitability as a control variable. 8) Profitability significantly affects tax planning 9) Leverage, company size, executive characteristics, and profitability as control variables significantly affect tax planning simultaneously.